1998
DOI: 10.1128/iai.66.2.874-877.1998
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Production by Cystic Fibrosis Isolates of Burkholderia cepacia

Abstract: Sixty-one Burkholderia cepacia isolates from patients with cystic fibrosis (CF) and four plant isolates were screened for production of the siderophores salicylic acid (SA), pyochelin, cepabactin, and ornibactins and fingerprinted by a PCR-based randomly amplified polymorphic DNA (RAPD) method. Of the 24 RAPD types determined, 22 (92%) were associated with isolates that produced SA, 21 (87%) were associated with isolates that produced ornibactins, 15 (60%) were associated with isolates that produced pyochelin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(89 citation statements)
references
References 21 publications
1
86
0
Order By: Relevance
“…The experiments were performed with Burkholderia cenocepacia H111 (LMG 23991), a clinical isolate from a cystic fibrosis patient 54 . This isolate (hereafter referred to as wild type) produces two siderophores, ornibactin and pyochelin 42,55 . This species further possesses a membrane-embedded siderophore-independent iron uptake mechanism 23 , which we did not focus on in this study because its contribution to iron uptake is relatively minor under the culturing conditions used.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed with Burkholderia cenocepacia H111 (LMG 23991), a clinical isolate from a cystic fibrosis patient 54 . This isolate (hereafter referred to as wild type) produces two siderophores, ornibactin and pyochelin 42,55 . This species further possesses a membrane-embedded siderophore-independent iron uptake mechanism 23 , which we did not focus on in this study because its contribution to iron uptake is relatively minor under the culturing conditions used.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed with Burkholderia cenocepacia H111 (LMG 23991), a clinical isolate from a cystic fibrosis patient (Gotschlick et al 2001). This isolate (hereafter referred to as wild type) produces two siderophores, ornibactin, and pyochelin (Darling et al 1998;Sokol et al 1999). This species further possesses a membrane-embedded siderophore-independent iron uptake mechanism (Mathew et al 2014), which we did not focus on in this study, because its contribution to iron uptake is relatively minor under the culturing conditions used.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Siderophore-mediated iron acquisition has been identified as an important virulence factor in members of the genus Burkholderia and was extensively studied in clinical isolates of B. cenocepacia (Thomas, 2007). They often produce two siderophores, pyochelin and ornibactin (Darling et al, 1998;Sokol et al, 1999) and these have been correlated with the ability of these strains to establish and maintain an infection (Sokol et al, 2000;Visser et al, 2004;Uehlinger et al, 2009). Previous studies have also shown that a single functional siderophore system is sufficient for growth of B. cenocepacia Pc715j in iron restricted conditions (Visser et al, 2004).…”
Section: Introductionmentioning
confidence: 99%